Improved Students’ Level of Achievement, Autonomy of Learning, and Metacognitive Strategies through Teaching Social Studies Using New Media - Lozanta Jr., Alfredo A. (Alipato, A Journal of Basic Education, 2022)
This study explored the relationship between teaching social studies and the use of new media technologies such as Genyo LMS, Facebook messenger, web-and-cloud-based software like  Lucidchart, Powtoon, Prezi, toondo.com, Wikimedia,  Rubistar, and Rubricmaker for assessment and improvement of students' level of achievement, autonomy of learning, and use of metacognitive strategies. Through the use of a one-group pretest-post-test design, and the administration of a Teacher-Made Assessment Test and a Self-Regulation Questionnaire-Academic to 35 Grade 9 students, it was revealed that the use of new media technologies in teaching social studies had a significant effect on the students' level of achievement, and that there was a substantial change in their autonomy of learning. Moreover, it showed that it had significant effects on the metacognitive strategies of students such as planning, evaluating, and reflecting. The results revealed a positive-weak correlation between the students' level of achievement and their autonomy of learning. Hence, researchers and educators are recommended to continue exploring other new media technologies that make the learning process more interesting and engaging for students. This study offers innovative approaches to teaching and learning social studies in the 21st century. Keywords: Social Studies, new media, achievement, autonomy of learning, metacognitive strategies